The Influence of Islamic Culture on Organizational Performance in Islamic University In Uganda: A descriptive Study - Mugoya Bashir; Ndizaawa Joash Paul; Akurut Patricia Ocom; Aina-Obe Shamsuddin Bolatito (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This paper set out to explore how everyday cultural practices and strong beliefs help shape how effective an institution can be, revealing layers of influence that aren’t immediately obvious. A mix of methods was used—from surveys and interviews to the analysis of various performance markers—so that both qualitative insights and hard numbers could be considered side by side. This study looks into how Islamic cultural values might influence organisational performance at Islamic universities in Uganda. Its focus is on understanding how everyday cultural practices and long-held beliefs can affect the way these institutions work; in most cases, both qualitative and quantitative data – gathered via surveys, interviews, and performance metrics analysis – will be used to tease out the link between Islamic cultural elements and organisational outcomes. The findings seem to point clearly to a link between using communal values, ethical behaviour, and leadership styles rooted closely in Islamic teachings and a boost in organisational results; in many cases, this translates into better employee morale, smoother collaboration, and a deeper sense of loyalty. Generally speaking, when cultural values are woven into everyday operations, the benefits seem to spill over quite naturally, especially in contexts where cultural identity holds major importance. It’s also worth noting that these insights aren’t limited to education; similar benefits could well be seen in the healthcare sector, where recognising and applying cultural principles might even improve organisational performance, patient satisfaction, and overall service quality. In all, by underlining the subtle yet meaningful impact of cultural nuances on building effective organisations, this study adds another voice to the wider debate on the need for management practices that truly respect and blend diverse cultural influences into their strategies.